Research in the Faculty of Dentistry "Raúl González Sánchez". 2011-2015. - Rosales Reyes, Sol Ángel; González Ramos, Rosa María; Raymundo Padrón, Edelis; Hernández Pedroso, Luis; Valverde Grandal, Orietta (Revista Habanera de Ciencias Médicas, 2017)
Introduction: Universities are an excellent space to make investigations. The main function is to generate new knowledge. Objective: To evaluate the performed actions and results achieved by the Investigation's Department of the Faculty of Dentristy "Raúl González Sánchez" of the Havana Medical University, during the period 2011 - 2015. Materials and Methods: A descriptive study was carry out at institutional level, of the actions performed and the results achieved of the Faculty's Investigation Department during the period 2011 - 2015. Were studied institutional actions done in favor of research as well as the variables associated with scientific research projects and publications performed. Results: Training workshops were held to prepare investigations projects, and publications and also workshop for the approval of 129 new projects. From those, 25,4% belong to Periodontics, 22,2% to Orthodontic, 18,3% to Prosthodontic and 16,3% to Integral General Stomatology. Release of scientific magazines to publish were: Refereed magazines (52.4%), of them, 22,2% in foreign magazines. 67,3% were new release. Conclusions: Between 2011 and 2015, research activity in the studied Faculty can be evaluated as satisfactory, due to there has been an increase in the number of research projects and the publications remained at similar levels for years, except 2015, in which they increased. The number of publications release from projects increased. More than half of the articles were published in refereed journals, the number of papers in foreign journals increased, and most were original articles. Keywords: Projects, investigations, publication, scientific production, faculty of dentistry.